Can the supido radar be used for measuring ball speed during soccer kicking? A reliability and concurrent validity study of a new low-cost device - Díez-Fernández, D. M.; Rodríguez-Rosell, D.; Gazzo, F.; Giráldez, J.; Villaseca-Vicuna, R.; Gonzalez-Jurado, J. A. (Sensors, 2022)
The aim was to analyze the reliability and validity of a low-cost instrument, based on a radar system, to quantify the kicking ball speed in soccer. A group of 153 male soccer players (under-13, n = 53; under-15, n = 54; under-18, n = 46) participated in this study. Each player performed three kicks on the goal in a standardized condition while the ball speed was measured with three different devices: one Radar Stalker ATS II® (reference criterion) and two Supido Radar® (Supido-front of the goal and Supido-back of the goal). The standard error of measurement (SEM) expressed as a coefficient of variation (CV) and the intraclass correlation coefficient (ICC) were employed for assessing the reliability of each instrument. Stalker and Supido-back showed very high absolute (CV = 4.0-5.4%) and relative (ICC = 0.945-0.958) reliability, whereas Supido-front resulted in moderate to low reliability scores (CV = 7.4-15%, ICC = 0.134-0.693). In addition, Lin`s concordance correlation coefficient (CCC) values revealed an `almost perfect` agreement between Stalker and Supido-back for the average (r = 0.99) and maximal (r = 0.98) ball speed, regardless of the ball speed range analyzed. However, Supido-front resulted in a poor degree of concordance (CCC = 0.688) and a high magnitude of error (17.0-37.5 km·h-1) with the reference Stalker radar gun. The Supido Radar® placed behind the goal could be considered a reliable and valid device for measuring ball speed in soccer.